2017
DOI: 10.1111/acer.13452
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Related Knowledge and Alcohol-Related Norms in 4- to 6-Year-Olds-Evidence from the Dutch Electronic Appropriate Beverage Task

Abstract: Four- to 6-year-olds already have knowledge about alcohol and its norms in adult culture. Insight into the development of children's alcohol-related knowledge and alcohol-related norms over time is required to investigate the transitions to alcohol expectancies, drinking motives, and alcohol initiation often occurring in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…To participate in the study, parents were asked to provide active consent either via a secured website (http://www.vol-onderzoek.nl) or on paper. Details about the fieldwork are described in Voogt and colleagues ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To participate in the study, parents were asked to provide active consent either via a secured website (http://www.vol-onderzoek.nl) or on paper. Details about the fieldwork are described in Voogt and colleagues ().…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, participating families were entered into a drawing for €100 (approximately $110). The Ethical Committee of the Faculty of Social Sciences of the Radboud University (ECSW2014‐2411‐272) approved this study's procedures, as described in Voogt and colleagues ().…”
Section: Methodsmentioning
confidence: 99%
“…Following the idea that knowledge, including social norms, are established well before consumption is first initiated, it has previously been demonstrated that an understanding of situational norms becomes first evident among considerably younger children. Children as young as four have been shown to be aware that alcohol consumption is more common at a party as opposed to when driving a car, that men drink more than women and that men drink beer [12]. In the Netherlands, Voogt et al [7] found that children attributed more alcoholic beverages to adults shown in common drinking situations (i.e.…”
Section: Person-specific and Situation-specific Normsmentioning
confidence: 99%
“…Subsequently, there have been calls for more research to examine other dimensions of children's beverage-specific knowledge [14]. Using the Dutch electronic Appropriate Beverage Task (eABT) [12], this paper aims to explore Dutch children's knowledge of beverage-specific situational norms. Specifically, we investigate what alcoholic beverages (i.e.…”
Section: Beverage-specific Knowledgementioning
confidence: 99%
“…According to the European School Survey Project on Alcohol and Other Drugs, approximately 47% of 15-16-year-old students had consumed alcohol and 8% had been drunk by the age of 13 (2). Exposure to alcohol starts from early on; children as young as 2-6 years old become aware of alcohol and related norms (3,4). Additionally, positive and/or negative explicit expectancies towards alcohol use have been shown to develop from the age of four (4).…”
Section: Introductionmentioning
confidence: 99%